2000
DOI: 10.1007/s002689910076
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Clinical and Laboratory Examinations in Patients with an Equivocal Diagnosis of Appendicitis

Abstract: In-hospital observation with repeated clinical examinations is commonly used in patients with an equivocal diagnosis of appendicitis. It is not known if repeated measurements of temperature and laboratory examinations have any diagnostic importance in this situation. The importance of repeated measurements of the body temperature, white blood cell (WBC) and differential cell counts, C-reactive protein concentration (CRP) and of the surgeon's repeated assessments was prospectively analyzed in 420 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
57
3
13

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 22 publications
9
57
3
13
Order By: Relevance
“…In our study many of the parameters are not commonly found, thereby lower scoring of Modified Alvarado score .Lower scoring may be the result of inability of the patient to define the symptoms well for low socioeconomic status. Traditional system of clinical diagnosis of acute appendicitis was highly sensitive (95.5%) in our study which was in concordance with previous studies where accuracy is between 76 and 92% [15][16][17] .…”
Section: Discussionsupporting
confidence: 81%
“…In our study many of the parameters are not commonly found, thereby lower scoring of Modified Alvarado score .Lower scoring may be the result of inability of the patient to define the symptoms well for low socioeconomic status. Traditional system of clinical diagnosis of acute appendicitis was highly sensitive (95.5%) in our study which was in concordance with previous studies where accuracy is between 76 and 92% [15][16][17] .…”
Section: Discussionsupporting
confidence: 81%
“…Leukocytosis was present in most patients in this study and was more frequent in patients with a diagnostic interval between 25 and 72 h. That was expected because the clinical evolution of appendicitis has its peak between 24 and 48 h after the onset [3,5,6,11]. Most patients in group 1 had leukocytosis which was also expected due to the initial phase of the inflammatory process [3][4][5][6]20]. Only 58 % of patients in group 4 had leukocytosis, and of those with leukocytosis, the value was high.…”
Section: Discussionmentioning
confidence: 54%
“…Although the absence of leukocytosis does not rule out appendicitis [3,21], its presence supports the clinical diagnosis [2][3][4][5][6][7][8]20]. It is expected that patients with advanced disease have higher WBC count due to increased polymorphonuclear cell count [5,12,20]. However, once the septic process is established, leukopenia may ensue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported diagnostic efficiency using physical exploration and lab studies vs. ultrasound and CT, demonstrating that when abdominal pain in the RLQ is assessed by a surgeon, sensitivity reaches more than 84%. 9,[15][16][17][18] Sonographers use graded compression and the three-step sequential positioning algorithm as a standard protocol. 6 In 12% of patients in this study, it was impossible to visualize the cecal appendix.…”
Section: Discussionmentioning
confidence: 99%